TINJAUAN SISTEMATIS PENERAPAN SISTEM INFORMASI PEMASARAN: ANALISIS LITERATUR MENGGUNAKAN PENDEKATAN PRISMA PADA ARTIKEL TERINDEKS SINTA TAHUN 2020–2025 - Nadia Dwi Astri; Vicky Brama Kumbara (Ensiklopedia of Journal, 2026)
Marketing Information Systems (MkIS) have become a strategic component for organizations seeking to design, execute, and evaluate their marketing activities amid an increasingly dynamic market. This article presents a systematic review of Indonesian scholarly literature on MkIS implementation published in SINTA-indexed journals between 2020 and 2025, aiming to map publication characteristics, reported benefits, and the obstacles organizations face in adopting such systems. A Systematic Literature Review (SLR) design was employed, following the 2020 Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) framework. Literature was retrieved from Google Scholar, Garuda, and the SINTA portal using the combined keywords "sistem informasi pemasaran," "sistem informasi manajemen pemasaran," and "marketing information system." After identification, screening, and eligibility assessment of 198 initial records, fourteen articles met the inclusion criteria for analysis. Findings indicate that MkIS adoption is consistently associated with more efficient marketing processes, sharper market segmentation and targeting, and stronger customer relationships and loyalty built on more structured customer data. Recent studies also point to a shift from conventional MkIS toward cloud-based platforms and more sophisticated marketing analytics. Meanwhile, the most frequently reported implementation challenges include the readiness of marketing personnel, limited cross-platform data integration, and a scarcity of quantitative studies measuring MkIS impact in measurable terms. This review recommends further quantitative, cross-sector research to strengthen the generalizability of findings on MkIS's contribution to organizational marketing performance.Keywords: marketing information system, marketing management, systematic review, PRISMA, SINTA literature